Agricultural biodiversity and coastal food systems: A socio-ecological and trans-ecosystem case study in Aurora province, Philippines - Alejos, Shan Faye; Pajaro, Marivic; Raquino, Mark; Stuart, Alex; Watts, Paul (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2021)
This paper presents a ridge-to-reef case study on Philippine biodiversity conservation that focused on reducing agricultural chemicals as a contribution to development goals of optimized food security, improving water quality, and mitigating maternal malnutrition. Building upon an earlier study that engaged participants and jurisdictions, farmers were oriented on biodiversity considerations and engaged in ecologically-based rodent management that was extended across the province of Aurora through the Office of the Provincial Agriculturist. Subsequently, a Participatory Action Research and Learning (PARL) cycle was conducted among 14 farmer participants to support biodiversity-friendly agriculture. Developed with local farmers, a biodiversity assessment demonstrated that organic approaches in rice farms increased arthropod biodiversity and reduced the number of key insect pests. The organizational results from this biodiversity study further indicated that local government participation can promote positive change by helping overcome the disconnect between communities and sustainability research. The approach to biodiversity-friendly agriculture reached a milestone through the collaborative development of an agricultural protected area supported by drafting a municipal ordinance to encourage the continued expansion of biodiversity-friendly agriculture and reductions in the chemical load of a key Aurora watershed. This paper discusses the biodiversity analysis and organizational results within the context of trans-ecosystem knowledge management and the goal of improving chronic maternal malnutrition that has been identified in coastal settlements of Aurora.